Using pulse oximeters in care homes for residents with COVID-19 and other conditions: a rapid mixed-methods evaluation - Manbinder Sidhu; Ian Litchfield; Robin Miller; Naomi J Fulop; Barbara Janta; Jamie-Rae Tanner; Giulia Maistrello; Jenny Bousfield; Cecilia Vindrola-Padros; Jon Sussex (NIHR Journals Library, 2022)
Background: There are over 15,000 care homes in England, with a total of approximately 450,000 beds. Most residents are older adults, some with dementia, and other residents are people of any age with physical or learning disabilities. Using pulse oximetry in care homes can help the monitoring and care of residents with COVID-19 and other conditions. Objectives: To explore the views of care home staff, and the NHS staff they interact with, with regard to using pulse oximetry with residents, as well as the NHS support provided for using pulse oximetry. Design: We carried out a rapid mixed-methods evaluation of care homes in England, comprising (1) scoping interviews with NHS leaders, care association directors and care home managers, engaging with relevant literature and co-designing the evaluation with a User Involvement Group; (2) an online survey of care homes; (3) interviews with care home managers and staff, and with NHS staff who support care homes, at six purposively selected sites; and (4) synthesis, reporting and dissemination. The study team undertook online meetings and a workshop to thematically synthesise findings, guided by a theoretical framework. Results: We obtained 232 survey responses from 15,362 care homes. Although this was a low (1.5%) response rate, it was expected given exceptional pressures on care home managers and staff at the time of the survey. We conducted 31 interviews at six case study sites. Pulse oximeters were used in many responding care homes before the pandemic and use of pulse oximeters widened during the pandemic. Pulse oximeters are reported by care home managers and staff to provide reassurance to residents and their families, as well as to staff. Using pulse oximeters was usually not challenging for staff and did not add to staff workload or stress levels. Additional support provided through the NHS COVID Oximetry @home programme was welcomed at the care homes receiving it; however, over half of survey respondents were unaware of the programme. In some cases, support from the NHS, including training, was sought but was not always available. Limitations: The survey response rate was low (1.5%) and so findings must be treated with caution. Fewer than the intended number of interviews were completed because of participant unavailability. Throughout the COVID-19 pandemic, care homes may have been asked to complete numerous other surveys etc., which may have contributed to these limitations. Owing to anonymity, the research team was unable to determine the range of survey respondents across location, financial budget or quality of care. Conclusions: Using pulse oximeters in care homes is considered by managers and staff to have been beneficial to care home residents. Ongoing training opportunities for care home staff in use of pulse oximeters would be beneficial. Escalation processes to and responses from NHS services could be more consistent, alongside promoting the NHS COVID Oximetry @home programme to care homes. Future research: Further research should include the experiences of care home residents and their families, as well as finding out more from an NHS perspective about interactions with care home staff. Research to investigate the cost-effectiveness of pulse oximetry in care homes, and of the NHS COVID Oximetry @home programme of support, would be desirable. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 35. See the NIHR Journals Library website for further project information.